Assessment Effect of Rosa Damascena Juice Aromatherapy on Elderly Chronic Musculoskeletal Pain in Sabzevar Retirement Clubs - Somayyeh Anbari; Zahra Estaji; Seddiqheh Rastaqhi (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Chronic pain is one of the major health issues during older age. Aromatherapy is a method to reduce such pain. The present study investigated the effects of inhaling rose extract on chronic musculoskeletal pain in elderly.  Methods & Materials The clinical trial consisted of 60 elderly individuals with chronic musculoskeletal pain, who were members of the retirement centers of Sabzevar city in 1395. The subjects were randomly allocated to two groups: intervention (31 people) and control (29 people). In the intervention group, the pain was measured using a McGill Pain Questionnaire. Before the intervention, interviews were conducted once a week on Thursdays by telephone for both groups. In the intervention group, the rose extract was inhaled using a linen handkerchief with a three-drop dip of the extract on it daily for three weeks. In the control group, sweet almond oil was used similarly. Data were analyzed using SPSS.  Results The present study showed that the inhalation of Rose extract did not affect the sensory and emotional aspect of pain in individuals; however, a statistically significant difference was noted in the sensory aspect between men and women (P<0.05) but not in the emotional dimension. Conclusion The present study showed that the inhalation of rose extract reduces the sensory dimension of chronic pain between men and women. Although additional investigation is imperative, these findings can be used for effective pain management interventions.